PENGARUH SIMPANAN ANGGOTA DAN PINJAMAN ANGGOTA TERHADAP SISA HASIL USAHA PADA KOPERASI SYARIAH SALMA KOTA CIMAHI - Denny Putri, Aulia Agnessthesa Denny Putri (JEBS (Journal of Economic and Business Student), 2023)
This research aimed to determine how much the effect of savings and loan numbers of members on the residual income at the Salma Sharia Cooperative in Cimahi City for the 2010–2021 period. The research method used was a descriptive method with a quantitative approach. The research population was Salma Sharia’s Cooperative annual financial report. Meanwhile, the research sample was the Salma Sharia Cooperative annual financial report study for the 2010-2021 period. The data analysis used in this study was a multiple regression analysis at a significance level of 5%. The program applied in analyzing the data used IBM SPSS Ver.25.00. The results showed that members of savings and loans affected the residual income. The results showed that member savings and member loans had an effect on the remaining operating income through the T test for X1 , a significance value of 0.005 < 0.05 was obtained, so it can be concluded that member savings (X1) had a partial effect on the remaining operating results (Y). The results of the T test for X2 obtained a significance value of 0.013<0.05, so it can be concluded that member loans (X2) have a partial effect on the remaining operating results (Y). The F-test obtained the value that the fcount > ftable, namely 4.774 > 4.10 with a significance value of 0.039 < 0.05. Thus, it can be concluded that there is an influence between members of savings and loans on residual income. The obstacles in the Salma Sharia Cooperative in Cimahi City were caused by the lack of participation from members in the lack of human resources in understanding computers. The solution suggested to cooperatives is improving human resources quality through computer science courses and training and increasing the number of deposits, loans, and residual income to fulfill members’ needs.